Juridical Review of A Sexual Violence Criminal Offense Committed by A Step Father Against A Stepchild - Arsa Putri, Icha Octaviani; Aryani, Esti; Susilawati, Endang Yuliana (PROCEEDING ICTESS (Internasional Conference on Technology, Education and Social Sciences), 2023)
This study aims to review the delibration process of The Panel of Judges in imposing a heavier sentence than the Prosecutor's demands forthe perpetrator of sexual violence criminal offense committed by a stepfather against a stepchild in Verdict of District Court of KefamenanuNumber 3/Pid.Sus/2023/PN Kfm. In imposing a sentence, the Panel of Judges must consider juridical and non-juridical circumstancesto impose a fair sentence for the defendant and the victim. This research is conducted by reviewing written norms with a case approachsupported by secondary data or library materials. The data were collected through a literature study and documentation. The method of dataanalysis in this study is descriptive qualitative method. The results of this study indicate that in imposing a verdict to the Defendant whocommitted the crime of sexual violence against his stepdaughter, the Panel of Judges has considered 3 (three) aspects, namely juridical,philosophical, and sociological considerations. The Panel of Judges is convinced to heighten the criminal penalties imposed on the Defendantbased on philosophical considerations. In philosophical considerations, the Panel of Judges considered that the urgency of sexual violence thatis often committed against children could threaten the crucial roles of children as the next generation of the nation in the future. Therefore,the Panel of Judges believes that imposing a heavier sentence than the Prosecutor's demands for the perpetrators of sexual violence crimes isexceptional in the court. In practice, judges commonly impose less or the same punishment as the charges of the Prosecutor in other existingverdicts.Keywords: judges’ considerations, sexual violence, criminal law, children